Keanu [videorecording (DVD)] - Peele, Jordan, 1979-; Key, Keegan-Michael, 1971-; Haddish, Tiffany, 1979-; Guzmán, Luis, 1956- (Warner Home Video, 2016)
Clarence and Rell, cousins who live in the city but are far from streetwise. When Rell's beloved kitten, Keanu, is catnapped, the hopelessly straight-laced pair must impersonate ruthless killers in order to infiltrate a street gang and retrieve the purloined feline. But the incredibly adorable kitten becomes so coveted that the fight over his custody creates a gang war, forcing our two unwitting heroes to take the law into their own hands.